Sweatshops: Economic Analysis and Exploitation as Unfairness - Sollars, Gordon G. (Journal of business ethics, 2018)
The economic and moral defense of sweatshops given by Powell and Zwolinski (J Bus Ethics 107:449–472, 2012) has been criticized in two recent papers. Coakley and Kates (J Bus Ethics 117:553–558, 2013) focus on putative weaknesses in the logic of Powell’s and Zwolinski’s argument. Preiss (Bus Ethics Quart 24(1):55–82, 2014) argues that, even granting the validity of their economic argument, Powell’s and Zwolinski’s defense is without force when viewed from a Kantian republican viewpoint. We are concerned that sweatshop critics have misinterpreted the economic literature and overstated the conclusions that follow from their ethical premises. We show that the best understanding of the current economic literature supports Powell’s and Zwolinski’s conclusions about the negative effects of sweatshop wage regulation, and that it is unreasonable to reject economic analysis in moral argument against sweatshops even from a Kantian perspective. Additionally, we defend the theory of exploitation as unfairness given by Wertheimer (Exploitation, 1996), and show how economic analysis can be applied to that theory to identify cases of sweatshop exploitation.